1998
DOI: 10.1182/blood.v91.2.706.706_706_709
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in a Cohort of Men Expressing the Glucose-6-Phosphate Dehydrogenase Deficiency

Abstract: The objective of this study was to test the hypothesis of a lower mortality from cancer and cardiovascular diseases among men expressing glucose-6-phosphate dehydrogenase (G6PD) deficiency. We designed a mortality study based on death certificates from January 1, 1982 through December 31, 1992 in a cohort of G6PD-deficient men. Cohort members were 1,756 men, identified as expressing the G6PD-deficient phenotype during a 1981 population screening of the G6PD polymorphism. The setting was the island of Sardinia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…It is noteworthy that our results do not confirm the results of previous investigations, which supported a significant protective effect of G6PD deficiency against cardiovascular diseases. 8,12,13 However, the differences in terms of results may be partly accounted for by different designs and methods. Our findings should be evaluated in light of some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that our results do not confirm the results of previous investigations, which supported a significant protective effect of G6PD deficiency against cardiovascular diseases. 8,12,13 However, the differences in terms of results may be partly accounted for by different designs and methods. Our findings should be evaluated in light of some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Associations were found between G6PD deficiency and cardiovascular risk (Cocco et al, 1998;Dore et al, 2021;Meloni et al, 2008;Pes et al, 2019) in conflicting directions. Regarding cancer, some studies found lower rate of cancer in G6PD deficient patients, while others found no difference (Cocco, 1987;Dore et al, 2016;Ferraris et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that G6PD-deficient individuals may be more predisposed to specific autoimmune diseases (Dore et al, 2023; Saha et al, 1982), infections (Abu-Osba et al, 1989; Mondal et al, 2022; Rostami-Far et al, 2016) and diabetes mellitus (Lai et al, 2017; Saha, 1979). Associations were found between G6PD deficiency and cardiovascular risk (Cocco et al, 1998; Dore et al, 2021; Meloni et al, 2008; Pes et al, 2019) in conflicting directions. Regarding cancer, some studies found lower rate of cancer in G6PD deficient patients, while others found no difference (Cocco, 1987; Dore et al, 2016; Ferraris et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, epidemiological studies suggest that individuals in the Mediterranean region carrying a loss-of-function G6PD variant are less susceptible to cardiovascular disease 14,15 . DNMTs and TETs affect gene expression under both normal physiological and disease conditions.…”
mentioning
confidence: 99%
“…At the same time, DNA hypomethylation and upregulated expression of nitric oxide synthase 3 (NOS3) and superoxide dismutase were observed in the G6PD S188F rats. In addition, epidemiological studies suggest that individuals in the Mediterranean region carrying a loss-of-function G6PD variant are less susceptible to cardiovascular disease 14,15 . DNMTs and TETs affect gene expression under both normal physiological and disease conditions.…”
mentioning
confidence: 99%